Consumerism and Conflict: Case Study of NCT 127 Fans on Twitter - Triasyoga, Videlia Suryaning; Trinugraha, Yosafat Hermawan; Nurhadi, Nurhadi (Sekolah Pascasarjana Universitas Brawijaya, 2024)
Twitter is a social media actively accessed by K-pop fans who interact with each other. However, these interactions can also lead to conflicts between fans, which is called fan wars. In the NCT 127 concert: The Link Jakarta held on November 4-5, 2022, various factors triggered fan wars ranging from the absence of queue numbers (QN) to the different treatment given by promoter D to NCT 127 fans (chilzennie) and NCT DREAM fans (dreamzennie). This research uses a qualitative method with a virtual ethnographic approach. The data analysis technique uses the Spradley model, which consists of 12 steps. The results showed that NCT 127 fans performed consumerism in The Link Jakarta concert activities and formed a consumption practice that both needed each other. Hills Retrieved the concept of fans as consumers and fan culture as a form of creating strong emotional ties with images and narratives that have been arranged to cause identity behavior in the context of the entertainment industry and pop culture such as K-Pop, the interaction between consumerism can produce a strong influence on fan activities such as fan war conflicts during concert activities. Keywords: fans, fan war, K-Pop, NCT, Twitter